Göttingen Minipig is not a Suitable Animal Model for in Vivo Testing of Tissue-Engineered Corneal Endothelial Cell-Carrier Sheets and for Endothelial Keratoplasty. (2nd August 2020) - Telinius, Niklas; Spinozzi, Daniele; Rasic, Dusan; Dapena, Isabel; Baandrup, Ulrik; Miron, Alina; Oellerich, Silke; Hjortdal, Jesper
ABSTRACT: Aim: To test the feasibility of implanting human anterior lens capsules (HALCs) with porcine corneal endothelial cells (pCEC) in vivo in Göttingen minipigs and at the same time test the suitability of Göttingen minipig as model for endothelial keratoplasty. Materials and Methods: Cell-carrier constructs of decellularized HALC with cultured (pCEC) were created for implementation in vivo . Eight Göttingen minipigs (6 months old) underwent surgery with descemetorhexis or removal of endothelium by scraping and implementation of HALC without (animal 1–4) and with (animal 5–8) pCEC. Follow-up examinations included optical coherence tomography (OCT) imaging (1, 2 and 3 months) and slit-lamp examination (<1 week as well as 1, 2 and 3 months). Results: Intraoperative challenges included difficulties in maintaining an anterior chamber due to soft tissue and vitreous pressure, development of corneal edema and difficulties removing Descemet's membrane because of strong adhesion to stroma. Therefore, descemetorhexis was replaced by mechanical scraping of the endothelium in animal 4–8. HALCs without pCEC were implanted in animal 1–4. Apposition to the back surface was not achieved in animal 1 and 3 because of corneal edema and poor visibility. Animal 5 was sacrificed because of a lens capsule tear. HALCs with pCEC were implanted in animal 6–8. Slit-lamp examination the first week revealed corneal edema in all animals, although mild in animals 4. One-month examination showed retrocorneal membranes with overlying corneal edema in all animals. Histology showed fibrosis in the AC and on the back surface of the cornea, compatible with the clinical diagnosis of retrocorneal membrane. Conclusions: In conclusion, the minipig is not suitable for corneal transplantation studies in vivo because of intraoperative challenges and development of retrocorneal membrane postoperatively. For in vivo testing of the surgical handling and the therapeutic potential of tissue-engineered endothelial cell-carrier constructs other animal models are required.